(p)ppGpp mediates persister formation in Escherichia coli during glucose to fatty acid shift - Zhang, Ruixue; Xiao, Zhengyang; Namburi, Neha; Tang, Yinjie; Yuan, Joshua; Zhang, Fuzhong (Frontiers in Microbiology, 2026)
Bacterial persistence contributes to antibiotic failure and recurrent infectious disease, yet the metabolic cues that promote persister formation remain poorly understood. Here we investigated Escherichia coli persistence after nutrient downshifts from glucose to various carbons. Compared to shifts to gluconeogenic carbons (pyruvate, malate, succinate, and fumarate), the glucose-to-fatty acid shift induced exceptionally high persister levels, with cells tolerating ampicillin (56%), carbenicillin (22%), and gentamicin (1%) after 24-h treatment. With an RNA-based biosensor and HPLC quantification, we detected up to 4-fold higher guanosine tetra- and penta-phosphate [(p)ppGpp] during the prolonged carbon starvation period post glucose-to-fatty acid shift, whereas (p)ppGpp levels remained low after glucose-to-gluconeogenic carbon shifts due to the shorter lag phase. Shortening the lag phase by pre-exposing cells to fatty acid substantially reduced persistence after the glucose-to-fatty acid shift. Overexpression of acyl-ACP synthase, which acylates free acyl carrier protein and thereby suppresses SpoT-dependent (p)ppGpp synthesis, lowered (p)ppGpp levels and reduced persistence. Furthermore, overexpression of PlsB, a growth-essential enzyme in phospholipid biosynthesis that is inhibited by (p)ppGpp, also reduced persistence. In addition, 13C isotope tracing and metabolomic analysis revealed that persisters remain metabolically adaptive, rerouting measurable carbon flux into gluconeogenesis and the pentose phosphate pathway for biomass synthesis. The metabolic remodeling could assist cells to balance redox homeostasis and mitigate oxidative stress. These findings establish the role of (p)ppGpp in nutrient shift persister formation and highlights critical pathways that may be targeted to reduce persistence and improve treatment outcomes against recurrent infections.